COMPARATIVE SCREENING OF ANTIBACTERIAL AND ANTIFUNGAL ACTIVITY OF SIX ETHNO-MEDICINALLY IMPORTANT PLANTS OF ASSAM - KANDARPA KR. SAIKIA; VEDANT V BORAH; M C KALITA; MANGALA LAHKAR (International Journal of Pharma and Bio Sciences, 2013)
Emergence of drug resistance amongst clinical isolates of bacteria and fungi has led to the need of search for alternate drug candidates. Medicinal plants are a source of antimicrobial agents and some of which have been used for centuries by tribes in Assam. In this study, extracts of six medicinal plants namely Cissus quadrangularis L., Moringa oleifera L., Ziziphus jujuba M., Cassia fistula L., Dillenia indica L., and Paederia foetida L. were tested for activity against clinical isolates of bacteria and fungi. The preliminary phytochemical analysis of the extracts was tested for the presence of alkaloids, glycosides, steroids, terpenoids, carbohydrates, amino acids and saponins. The extracts were subjected to screening of in vitro antibacterial and antifungal activity against selected clinical isolates viz. Staphylococcus aureus, Streptococcus pneumoniae, Escherichia coli, Klebsiella pneumoniae, Candida albicans and Candida trophicalis. All the extracts exhibited inhibitory activity against the test pathogens. For positive control, a standard disc containing antibiotic drug Amoxicillin (10µg/disc), Kanamycin (30µg/disc) and Ketoconazole (50µg/disc) was used.